Study of severe anemia in hospitalized children in Ahmedabad (Gujarat), India - Harsh J. Muliya; Maulika V. Shah; Hetal N. Jeeyani; Dudhia, Divy H.; Arjun J. Jalandhra (International Journal of Contemporary Pediatrics, 2023)
Background: Anemia is a major nutritional problem worldwide especially in developing countries. This research was conducted to find the incidence of severe anemia, to identify the common clinical features and etiology of it and to assess the requirement of packed red cell transfusion. Methods: All patients having severe anemia (hemoglobin <7 gm/dl in 6-59 months and <8 gm/dl in 5-14 years as per WHO definition) between 6-14 years were included in this study. Detailed medical history, anthropometric measurements and clinical examination were done. Complete blood count, peripheral smear, reticulocyte count and stool microscopy were done in all patients. Then anemia classified morphologically into microcytic, normocytic, macrocytic and dimorphic. Further investigations were done according to the peripheral smear to identify the etiology of severe anemia. Results: During the study period, 84 patients of severe anemia were hospitalized with incidence of 2.57%. It was more common in male in 6 months to 5 years and in female in 10-14 years age. 67% patients had microcytic, 28% had dimorphic and 2.5% each had normocytic and macrocytic anemia. The most common anemia was iron deficiency (82%) followed by anemia of chronic disease (17%), hemolytic anemia (12%), megaloblastic anemia (7%) and blood loss anemia (1%). Packed red cell transfusion was required in 16 (19%) patients with severe anemia. Conclusions: Good clinical examination with peripheral smear is helpful in classifying the anemia morphologically. Following this, the use of investigations as per the standard flow charts, helps in identification of etiology.